A Case Study on Kelang Port Management Sdn. Bhd. Setting Up its First Joint Venture Subsidiary Company in Cambodia - Wong, Pun Yoke (1997)
Halim Harun, the Chief Executive Officer of Kelang Port Management (KPM) was very happy when he left the Board Room one evening in late June 1997, . noted his Personal Assistant. What pleased him was not the number of papers approved by the Board on that day but that the Directors did not reject his proposal paper to set-up a joint-venture subsidiary company in Cambodia. According to Halim, KPM's proposal was to manage and operate the Inland Port in Phnom Penh on a joint-venture basis with a local partner.